Phenolic Compounds and Antioxidant Activity of Different Organs of Potentilla fruticosa L. from Two Main Production Areas of China. Issue 9 (17th August 2016) - Yu, Danmeng; Pu, Wenjun; Li, Dengwu; Wang, Dongmei; Liu, Qiaoxiao; Wang, Yongtao
Abstract : This report compared the phenolic compounds and antioxidant activity of the leaves, flowers, and stems of Potentilla fruticosa L. collected from two main production areas of P. R. China (Taibai Mountains and the Qinghai Huzhu Northern Mountains). The results indicated that there were significant differences in the phenol contents and antioxidant activities among the different organs and between the two productions. High‐performance liquid‐chromatography analysis indicated that hyperoside, (+)‐catechin, ellagic acid, and rutin were the primary compounds in leaves and flowers; for stems, the content of six phenolic compounds, from two productions, were the lowest. The 1, 1‐diphenyl‐2‐picryl hydrazyl (DPPH), 2, 2‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid) di‐ammonium salt (ABTS), ferric reducing power (FRAP), lipid peroxidation assays, and microbial test system (MTS) were used to evaluate the antioxidant activity. The results demonstrated that the leaves from two productions exhibited powerful antioxidant activity than other organs, which did not significantly differ from that of the positive control (rutin), followed by the flowers and stems. The correlation between the content of phytochemicals and the antioxidant activities of different organs showed that the total phenol, tannin, hyperoside, and (+)‐catechin contents may influence the antioxidant activity, and these compounds can be used as markers for the quality control of P . fruticosa .